2013
DOI: 10.1111/1467-9566.12043
|View full text |Cite
|
Sign up to set email alerts
|

Undoing gender? The case of complementary and alternative medicine

Abstract: Despite a rich body of sociological research that examines the relationship between gender and health, scholars have paid little attention to the case of complementary and alternative medicine (CAM). One recent study (Sointu 2011) posits that men and women who use CAM challenge traditional ascriptions of femininity and masculinity through the exploration of self-care and emotions, respectively. Drawing on 25 in-depth interviews with middle-class Americans who use CAM, this article instead finds that men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
(75 reference statements)
1
26
1
1
Order By: Relevance
“…), as well as by the presence or absence of a female spouse (McEvoy and Richardson ). Considering the association of weight loss and WLS with femininity, these men may have attributed the decision to undergo WLS to their wives as a way of establishing a credible masculine identity (Courtenay ), as also noted in a study of women and men's use of complementary and alternative medicine (Brenton and Elliott ). As Robertson and Monaghan (: 154) write, ‘many men may be “giving over” responsibility for their health to female partners or relatives in a manner that confirms and maintains the traditional gender roles of both’.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…), as well as by the presence or absence of a female spouse (McEvoy and Richardson ). Considering the association of weight loss and WLS with femininity, these men may have attributed the decision to undergo WLS to their wives as a way of establishing a credible masculine identity (Courtenay ), as also noted in a study of women and men's use of complementary and alternative medicine (Brenton and Elliott ). As Robertson and Monaghan (: 154) write, ‘many men may be “giving over” responsibility for their health to female partners or relatives in a manner that confirms and maintains the traditional gender roles of both’.…”
Section: Resultsmentioning
confidence: 96%
“…However, self‐care is strongly coded as a feminine project. While women are able to draw on their emotions to account for their pursuit of self‐transformation through WLS, men are expected to distance themselves from the emotional aspects of self‐care (Brenton and Elliott ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Australia, a 2007 survey found that CAM use was more common among females, yet in a lower (18–35 years) age bracket [11]. Women comprised almost 70% of the sample and are known to seek CAM therapy for a wider range of problems than do men [12]. …”
Section: Discussionmentioning
confidence: 99%
“…). Even patients seeking non‐traditional forms of care often wind up reproducing gendered identities by striving for ideals like personal control (Brenton and Elliott ), which while not exclusively a neoliberal idea remains a central element of the ideology. In addition to being gendered (Williams ), these values are inherently raced and classed (Melamed ).…”
Section: Illness Managementmentioning
confidence: 99%
“…I also still tend to 'cope' with more difficult aspects of illness management by reinforcing ideals of independence and personal responsibility, which represent core themes in neoliberalism (see Lareau 2003, Schwalbe et al 2000. Even patients seeking non-traditional forms of care often wind up reproducing gendered identities by striving for ideals like personal control (Brenton and Elliott 2014), which while not exclusively a neoliberal idea remains a central element of the ideology. In addition to being gendered (Williams 2013), these values are inherently raced and classed (Melamed 2006).…”
Section: Internalised Illness Management Aspirations and Expectationsmentioning
confidence: 99%